2020
DOI: 10.1002/mp.14497
|View full text |Cite
|
Sign up to set email alerts
|

Report of AAPM Task Group 235 Radiochromic Film Dosimetry: An Update to TG‐55

Abstract: The use of radiochromic film (RCF) dosimetry in radiation therapy is extensive due to its high level of achievable accuracy for a wide range of dose values and its suitability under a variety of measurement conditions. However, since the publication of the 1998 AAPM Task Group 55, Report No. 63 on RCF dosimetry, the chemistry, composition, and readout systems for RCFs have evolved steadily. There are several challenges in using the new RCFs, readout systems and validation of the results depending on their appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
273
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(291 citation statements)
references
References 357 publications
(1,376 reference statements)
2
273
2
1
Order By: Relevance
“…[197][198][199][200][201] In view of this controversy, it is advisable to strictly adopt all the precautions needed for radiochromic film dosimetry. 123,192…”
Section: Two-dimensional Passive Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[197][198][199][200][201] In view of this controversy, it is advisable to strictly adopt all the precautions needed for radiochromic film dosimetry. 123,192…”
Section: Two-dimensional Passive Detectorsmentioning
confidence: 99%
“…126,231,232 However, the parallel irradiation of the Gafchromic™ EBT films is discouraged by Fontanarosa et al 233 who observed unacceptable under dosage in PDD at depths greater than 15 cm (about 5% at 20 cm). In general, the detectors that have smallest k f clin, f msr Q clin, Q msr factor (microdiamond, microslicon, plastic scintillator, EBT film) 78,85,97,123,156,158,[186][187][188]192,[234][235][236] are preferred to avoid the need to correct the PDD. If the institution is unable to justify acquisition of at least one of these systems, the method described by Francescon et al 237 and as described in Figure 5 could be adopted.…”
Section: Percentage Depth Dose (Pdd)mentioning
confidence: 99%
“…However, for doses larger than 10 Gy and up to 40 Gy, EBT-XD films are preferred. 10 EBT3 and EBT-XD films are considered energy independent for MV photon beams. However, they under-respond to photon energies lower than 100 keV 8 , and exhibit LET dependence for protons.…”
Section: Radiochr Omic Filmsmentioning
confidence: 99%
“… 9 , 10 More recently, sensitive self-developing films such as GAFchromicExternal Beam Therapy (EBT) have been developed by Ashland that are based on the lithium salt of PCDA (Li-PCDA) 11 18 and span dose ranges of 0.01–40 Gy. 1 , 2 , 19 As the more recent models of GAFchromic EBT films (especially EBT3 and EBT-XD) exhibit high spatial resolutions, 20 , 21 near-tissue equivalence, 21 , 22 and dose rate and energy dependence 23 , 24 along with being insensitive to visible light, 25 they are routinely employed in low-dose gradient (e.g., a quality assurance tool in intensity-modulated radiation therapy) 25 28 and high-dose gradient settings (e.g., brachytherapy 29 , 30 ). 18 , 23 , 31 Therefore, continued research into photoactive ingredients with a tunable reactivity is very important to improve dosimetry technologies for different therapeutic uses.…”
Section: Introductionmentioning
confidence: 99%